The Impact of Using Artificial Intelligence in Learning on Students' Critical Thinking Skills: A Literature and Public Sentiment Analysis Study - Syahputra, Fahmy; Sabrina, Elsa; Simbolon, Angga Baginda; Nasution, Aulia Rivansy; Hutagalung, Namira Rahmadina; Amanda, Nayla; Siboro, Sari Agustina; Sirait, Steven (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to analyze the impact of the use of artificial intelligence (AI) in learning on students' critical thinking skills. Using a literature analysis approach and public sentiment study, this study identifies trends and findings from previous studies related to the integration of AI in education and its impact on students' cognitive abilities, especially in terms of critical thinking. Public sentiment studies focus on understanding public perceptions and views on the use of AI in the context of learning and its impact on students' critical thinking skills. The results of this study are expected to provide comprehensive insight into the potential benefits and challenges faced in the use of AI in education, as well as its implications for the development of students' critical thinking skills. In addition, this study has the potential to offer recommendations regarding effective learning policies and strategies to maximize the benefits of AI in improving students' critical thinking skills.